ANALISIS TRANSPARANSI PENGELOLAAN KEUANGAN PEMERINTAH DAERAH BERBASIS WEBSITE DI KABUPATEN GROBOGAN - Khabib, Rizal Maulana; Purbasari, Heppy (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The government can make regional financial management transparent by using a website. This research aims to determine the transparency of website-based regional government financial management in Grobogan Regency in 2013-2022. This research includes descriptive research, namely to analyze the transparency of website-based local government financial management in Grobogan Regency into three indicators, namely planning, implementation along with reporting and accountability. The data used is secondary data. Meanwhile, the data collection techniques used are documentation and interviews. The data analysis technique used is qualitative analysis. The research results show that website-based analysis of regional government financial management transparency in Grobogan Regency in 2013-2022 shows that the average level of transparency in regional government financial management is sufficient (available).